2015
DOI: 10.1097/sla.0000000000001480
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Art on Surgical Patients

Abstract: Objectives: The aim of the study was to assess the effect of art including ambient features such as music, interior design including visual art, and architectural features on health outcomes in surgical patients. Background: Healing environments can have a positive influence on many patients, but data focusing on art in surgical patients remain scarce. Methods: We conducted a systematic search following the PRISMA guidelines from January 2000 to October 2014 on art in surgical patients. For music interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 89 publications
4
12
2
Order By: Relevance
“…The results of this systematic review indicate that music exposure can exert positive effects on rodents' neurological, behavioral, immunological, and physiological outcomes. These results are broadly consistent with studies in humans that found that music exposure can positively affect brain structure and chemistry (Johansson, 2011; Yeh et al, 2015), behavioral read-outs (Chan et al, 2011; Thoma et al, 2013; Baird and Samson, 2015; Hole et al, 2015; Vetter et al, 2015), immunological responses (Conrad et al, 2007; Fancourt et al, 2014), and physiological parameters (Bekiroglu et al, 2013; Hole et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of this systematic review indicate that music exposure can exert positive effects on rodents' neurological, behavioral, immunological, and physiological outcomes. These results are broadly consistent with studies in humans that found that music exposure can positively affect brain structure and chemistry (Johansson, 2011; Yeh et al, 2015), behavioral read-outs (Chan et al, 2011; Thoma et al, 2013; Baird and Samson, 2015; Hole et al, 2015; Vetter et al, 2015), immunological responses (Conrad et al, 2007; Fancourt et al, 2014), and physiological parameters (Bekiroglu et al, 2013; Hole et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…They have been widely investigated in humans and can be linked to reduced depression levels in older people (Chan et al, 2011), to reduced disruptive behaviors and anxiety, and improved cognitive functioning in patients with dementia (Chang et al, 2015). A large number of studies have shown that music interventions alleviate anxiety and pain around medical procedures (Hole et al, 2015; Vetter et al, 2015) and surgical procedures (Kuhlmann et al, 2018). Music may have a beneficial effect on anxiety, systolic blood pressure, heart-rate, respiratory rate, quality of sleep, and pain in patients with coronary heart disease (Bradt et al, 2013), and might reduce blood-pressure in chronic hypertension (Kuhlmann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that music has a significant effect on the patient's pain, anxiety, and heart rate after surgery [2]. Whether this is true for other art forms has not been much investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Hospitals are more and more designed not only as functional buildings in which all technical standards of patient care and treatment can easily be met, but as total healing environments [1]. A systematic review and meta-analysis of studies on the outcome of patients exposed to art has shown that music, interior design, and architecture had a positive effect [2]. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some researchers have opted for pre-selected (i.e., researcher-selected) music pieces in the context of pain management such as slow, classical music, since this is believed to be perceived as relaxing and pleasant by most individuals [e.g., ( 78 )]. Others offered participants to choose pieces from a variety of musical genres in order to permit some degree of personal preference [e.g., ( 79 , 80 ), see also ( 81 )]. Overall, self-selected music has been shown to be superior to music chosen by researchers/clinical staff for pain alleviation in patients with chronic pain conditions ( 14 ) and to be superior to other distracting and emotionally engaging stimuli in experimental studies with healthy participants ( 24 ).…”
Section: Introductionmentioning
confidence: 99%